Konsep Homo Economicus dalam Al-Qur’an Surah An-Nisa Ayat 2-6 - Rorizki, Fitri; Tarigan, Azhari Akmal; Syahriza, Rahmi (Faculty of Islamic Religion, Universitas Muhammadiyah Sumatera Utara, 2024)
The concept of homoeconomicus studies has shortcomings that can be seen clearly when viewed rationally. This research uses a qualitative approach and is a type of library research or library research. Which is a type of research whose findings are not obtained through quantitative procedures and uses data analysis methods in the form of content analysis. The results of this research are that Homoeconomicus is an attitude that will never be satisfied, has needs and desires, has a preference to behave based on individual interests, is efficient (considering costs and benefits obtained. and is unable to take care of assets (su'u tasharruf). Islam has regulates the care of orphans in the Al-Qur'an. As for people who are given a will or given the task of caring for, looking after and caring for orphans, they are called guardians as contained in the Al-Qur'an, surah an-nisa verses 2-6, the author can conclude that the verse contains capable values applied in everyday life, the values contained in this verse include: Loving orphans, not giving authority to the safih group, always giving infaq, speaking kind words, being fair and not consuming the wealth of orphans.